2016
DOI: 10.1007/978-3-319-45117-6_31
|View full text |Cite
|
Sign up to set email alerts
|

Logistics Dynamics and Demographic Change

Abstract: Change and dynamics in logistics are interestingly driven at the same time by external as well as internal forces. This contribution outlines a big data literature review methodology to overview recognizable external changes and analyzes the interaction of one major trend-demographic change-further in order to allow for change management and adaption concepts for successful logistics. Therefore, this may be a first blueprint of how to analyze and react to specific trends in a holistic manner embedded into a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Because supply chain management (SCM) and logistics have often been addressed alongside each other in a broad array of journals [86], we conducted a parallel in-depth analysis [87]. Again, we utilized the data platform ''Web of Science'' because the contents of that database are often characterized by high-quality measures and the retrieval algorithms that can be formulated offer a relatively high degree of flexibility.…”
Section: Detection Of Major Trends In Logistics and Trend Interactmentioning
confidence: 99%
“…Because supply chain management (SCM) and logistics have often been addressed alongside each other in a broad array of journals [86], we conducted a parallel in-depth analysis [87]. Again, we utilized the data platform ''Web of Science'' because the contents of that database are often characterized by high-quality measures and the retrieval algorithms that can be formulated offer a relatively high degree of flexibility.…”
Section: Detection Of Major Trends In Logistics and Trend Interactmentioning
confidence: 99%
“…The literature has shown that logistics competitiveness is strongly related to trade expansion, export diversification, direct foreign investment and economic growth. The description of competitiveness is difficult for researchers, because organizations have many and often overlapping targets [12][13][14][15][16][17]. Some of these may include: Quality [13], Vendor performance [14], Productivity [15], Efficiency [16], Competitive position [18], Operating performance [19], Distribution effectiveness [20,21], Raw financial statistics (e.g., net income, gross sales), Cost statistics (e.g., transport cost, standard labor costs), firm evaluation [22], waste management [23], and input/output measures or performance criteria (e.g., number of shipments/vehicle hour) [12], etc.…”
Section: Logistics Competitiveness Evaluationmentioning
confidence: 99%
“…Based on the empirical findings in the survey (Klumpp et al 2014), two new regression models for dependent variables were developed: one regarding the dependent factor of recommendation for the truck drivers job towards others (Figure 5); and another regarding the dependent factor if drivers assume that they will be able to continue their job until retirement under the current working conditions (Figure 6). Both dependent factors are a representation of the truck drivers work motivationand in each case, three statistically significant independent and influencing factors were identified from all variables within the survey.…”
Section: Motivation Modelling For Truck Drivingmentioning
confidence: 99%